Cook it in cast iron : kitchen-tested recipes for the one pan that does it all (America's Test Kitchen, 2015)
"The cast-iron skillet is a sturdy, versatile, traditional kitchen workhorse that 85% of us own but far fewer of us reach for daily, mostly because we have one or two recipes we use it for and otherwise it stays in the back of the cabinet. In this new cookbook, the editors of Cook's Country will show you everything you need to know about cast-iron cookware and the many (and often surprising) dishes you can cook and bake in this multitasker of a pan, from the classic dishes everyone knows and loves like steak, perfect fried eggs, and cornbread, to innovative and inspiring recipes like skillet apple pie, pizza, and cinnamon swirl bread. Learn about this cast iron's history and what makes it uniquely American and let us show you how to shop for, season, care for, and clean this perfect pan,"--Amazon.com.